2004
DOI: 10.1158/0008-5472.can-03-3861
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Raf Kinase Inhibitor Protein Expression Is Associated with Increased Ras-Extracellular Signal-Regulated Kinase Signaling in Melanoma Cell Lines

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
148
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 22 publications
10
148
0
1
Order By: Relevance
“…Immunohistochemical analysis has demonstrated that the loss of RKIP expression is a key phenotype for many human cancers, including colorectal cancer, breast cancer, melanoma, prostate cancer and hepatocellular carcinoma, modulating distant metastasis, lymphatic metastasis, vascular infiltration and cancer mortality (45)(46)(47)(48)(49). Consistent with these studies, the present study showed that the incidence of positive RKIP expression in ESCC tissues was significantly less compared with the matched normal tissues, and that it was clinically correlated with lymph node metastasis.…”
Section: Rkip Protein Expression ------------------------------------supporting
confidence: 89%
See 1 more Smart Citation
“…Immunohistochemical analysis has demonstrated that the loss of RKIP expression is a key phenotype for many human cancers, including colorectal cancer, breast cancer, melanoma, prostate cancer and hepatocellular carcinoma, modulating distant metastasis, lymphatic metastasis, vascular infiltration and cancer mortality (45)(46)(47)(48)(49). Consistent with these studies, the present study showed that the incidence of positive RKIP expression in ESCC tissues was significantly less compared with the matched normal tissues, and that it was clinically correlated with lymph node metastasis.…”
Section: Rkip Protein Expression ------------------------------------supporting
confidence: 89%
“…Keller et al reported that RKIP expression was at its highest in normal prostate tissues, decreased in primary prostate cancers and was not detectable in metastatic tissues from prostate cancer (50). In addition, Schuierer et al demonstrated that RKIP expression was decreased concomitantly with the metastasis of melanoma (47). Mechanistic studies have suggested that RKIP is a metastasis suppressor gene that is responsible for blocking several signaling pathways in the metastatic cascade, including MEK, G proteins and NF-κB (51).…”
Section: Rkip Protein Expression ------------------------------------mentioning
confidence: 99%
“…On the molecular level, RKIP functions by inhibiting the proliferative and survival Raf-MEK-ERK and NF-kB signaling pathways (Chatterjee et al, 2004;Park et al, 2005). Consistent with its demonstrated inhibitory effect on Raf and NF-kB signaling, we and others have shown that the expression levels of RKIP are downregulated in a number of tumors, including highly metastatic prostate, breast and colon cancer, hepatocellular carcinoma, melanomas and insulinomas (Fu et al, 2003;Chatterjee et al, 2004;Schuierer et al, 2004Schuierer et al, , 2006Zhang et al, 2004;Hegan et al, 2005;Al-Mulla et al, 2006;Lee et al, 2006). The importance of RKIP in metastases was highlighted by the finding that restoration of RKIP expression inhibits prostate cancer metastasis in a murine model (Fu et al, 2003(Fu et al, , 2005.…”
supporting
confidence: 58%
“…Subsequent studies showed that overexpression of RKIP in prostate and melanoma cell lines suppresses metastasis by decreasing vascular invasion (18,20). Previous studies have described low levels of RKIP in other metastatic tumors, such as breast and colorectal carcinoma (23,45), as well as in many other primary tumors, including GISTs (27), insulinoma (22), hepatocarcinoma (24), ovarian carcinoma (26), merckel cell carcinoma (16) and thyroid carcinoma (15), cutaneous squamous cell carcinoma (46) and nasopharyngeal carcinoma (17).…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 99%
“…In cancer, RKIP is considered to be a signal transduction modulator and a metastasis suppressor (14), and down regulated in several human tumors, mainly in highly metastatic carcinomas (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Noteworthy, RKIP has been shown to be a prognostic marker in prostate cancer, colorectal carcinomas, gliomas and GISTs (25,(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%